(untitled) (Advancements in Homeopathic Research, 2022)
Specific phobia is normal reaction to the stress and can be beneficial in some of situations. It can alert us to dangers and helps us prepare and to pay attention. The Anxiety disorders differ from a normal feeling of nervousness or the anxiousness, and involve excessive fear ora anxiety.